RELIGION, LIFE, AND DEATH; UNTANGLING FEARS AND THE SEARCH FOR COHERENCE - Leong, Pamela (ABINGDON : ROUTLEDGE, 2022)
Based on a content analysis of writing assignments from a class on death and dying, this book focuses on the manner in which college students use religion to make sense of death and the dying process. Drawing on research spanning five years, the author considers the attitudes, concerns, and beliefs about death, exploring students' perspectives on the place of religion in end-of-life issues. With attention to questions related to death anxiety, suicide, mass homicide, and the death of young children, the author examines the ways in which students draw on religion to make sense of death, religion's function as both a source of comfort and empowerment and a source of distress, as well as the perceptions of those who resist religion. As such, Religion, Life, and Death will appeal to social scientists with interests in the sociology of young adults, and the sociology and psychology of religion, death, and dying.
Keywords: Death -- Religious aspects; SOCIAL SCIENCE / Sociology of Religion